Economic Efficiency of Housing Construction. Environmental Impact - AZHIGUZHAYEVA, Assel; BASSHIEVA, Zhangul; MALGARAYEVA, Zhanat (Journal of Environmental Management and Tourism, 2021)
The relevance of the research topic is due to the fact that, faced with the growing threat of global climate change, depletion of natural resources and the collapse of the global ecosystem, at the moment, in particular, the global construction industry is at the stage of an unprecedented test of strength. Going forward, Green Standards aim at the extremely difficult task of looking at environmental economics from end to beginning, i.e. from the end of the life cycle of a building or its complete utilization with the calculation of all energy spent in the process of design, construction, operation and utilization, processing. Kazakhstan is among the countries actively promoting the ideas of green growth and the transition to a green economy.